Desconuidades na conversação: as reformulações na constituição do diálogo do chat - Rodrigues, Valter Pinheiro (2006)
The Internet belongs to the quotidian of the society and it brings communicative and social references that request studies that can explain the establishment of this new support in the human development. From the theme Discontinued in the conversation: the reformulations in the constitution of the dialogue in the chat this research investigates, in a synchronous perspective, in the exploration in the interaction by means the language produced during the computer-mediated communication. The corpus in this study consists of two documented samples as of the thematic chat named Brazilian problems in which the interectants, spontaneously, dialogue in written. We investigate some aspects of the computer-mediated communication with the intention of corroborating with the scientific records that point to some regularities in the processing of the synchrounous interaction that is accomplished by means of the written language with evident marks from orality. In this study, we base theoreticaly in the socialinteractionist tendency from the linguistic studies. We investigate the extracted corpus from the Internet as of the application of the built theories in the set of the works that involves Analysis of Conversation and that deals with the topic organization and of the strategies of textual reformulation used by the speakers. From the attempt of assuring the intercomprehension of the conversational text and the construction of the social relation in the virtual interaction environment , the users of the chat accomplish to the use of the language, basing on the linguistc knowledge from their experiences as speakers in several situations in the face to face communication